Sorbic, benzoic and propionic acids in fishery products: a survey of the South Korean market. Issue 6 (3rd June 2018) - Kim, Dan-Bi; Jang, Gwang-Ju; Yoo, Miyoung; Lee, Gunyoung; Yun, Sang Soon; Lim, Ho Soo; Kim, MeeKyung; Lee, Sanghee
ABSTRACT: This study was conducted to provide basic data as part of a project to distinguish naturally occurring organic acids from added preservatives. Accordingly, we investigated naturally occurring levels of sorbic, benzoic and propionic acids in fish and their processed commodities. The levels of sorbic, benzoic and propionic acids in 265 fish and their processed commodities were determined by high-performance liquid chromatography–photodiode detection array (HPLC-PDA) of sorbic and benzoic acids and gas chromatography-mass spectrometry (GC/MS) of propionic acid. For propionic acid, GC-MS was used because of its high sensitivity and selectivity in complicated matrix samples. Propionic acid was detected in 36.6% of fish samples and 50.4% of processed fish commodities. In contrast, benzoic acid was detected in 5.6% of fish samples, and sorbic acid was not detected in any sample. According to the Korean Food and Drug Administration (KFDA), fishery products and salted fish may only contain sorbic acid in amounts up to 2.0 g kg −1 and 1.0 g kg −1, respectively. The results of the monitoring in this study can be considered violations of KFDA regulations (total 124; benzoic acid 8, propionic acid 116). However, it is difficult to distinguish naturally generated organic acids and artificially added preservatives in fishery products. Therefore, further studies are needed to extend the database for distinction of naturally generated organic acids and added preservatives. GRAPHICAL ABSTRACT: